On the Benefits of Rational Simplicity: How to Teach Humanities in Technical Universities? - E. N. Ivakhnenko; N. I. Kuznetsova (Высшее образование в России)
The article continues the discussion of teaching humanities disciplines in technical universities, which has been going on for several years on the pages of our journal. First of all, the authors object to raising the question of teaching humanities knowledge in technical universities “in general” and reject the unambiguous recommendations and prescriptions addressed to teachers “for all occasions”. The authors’ position can be formulated as a search and selection of cases that are most appropriate for promoting the overlapping cultures of science/engineering/technical and humanities. They share their approaches to the problem outlined against the background of critical reflection on A.A. Polonnikov’s article published in the same issue. Contradicting their colleague in the teaching profession, the authors emphasize the importance of the humanities teacher’s creativity and at the same time defend the principle of recursive continuity (“rational simplicity”) once proclaimed by Michel Foucault: “Not all discursive strategies are equally possible, but only those that are allowed by the preceding levels”.